Production Technology for Oat Protein with Advanced Physicochemical, Functional, and Technological Properties - Kashirskich E.; Babich O.; Kriger O. (Техника и технология пищевых производств, 2019)
The current intensive industrialization has changed the food preferences of consumers. As a result, there is a growing demand for high-grade high-nutritional meat and dairy products, which, in its turn, triggered an increase in the demand for grain crops and led to higher animal feed prices. All these affected the price and quality of the finished product, since farms are trying to stay profitable. As a consequence, the high cost of animal proteins make producers look for other sources of protein with similar qualities. Common oat (Avena sativa L.) remains the most cultivated species. Oats are a source of high-quality protein with an optimal amino acid balance. The paper features a oat protein technology (Avena sativa). The research defined the parameters of the protein extraction process. For acid and alkaline methods, the following optimum parameters were revealed: temperature – 40 ± 2°C, hydraulic module – 1:10, time – 90 minutes, active acidity of the acid extraction – 2.0 units, active acidity of alkaline extraction – 9.0 units. The authors managed to obtain protein substances with the molecular weight > 50 kDa. The optimal parameters of ultrafiltration of the protein extract were as follows: pore diameter = 100 kDa at pH 8.0 and 0.5 MPa. The ultrafiltration conducted under these conditions showed that the content of high molecular fractions (globulins and albumins) increased from 39.12% to 55.15% for the extract obtained by alkaline method, whereas the content of low molecular weight fractions (prolamins and glutelins) decreased from 60.88% to 44.85%. Ultrafiltration of protein extracts obtained by alkaline and acidic methods made it possible to concentrate protein fractions with a molecular weight ≥ 50 kDa. When a 10% aqueous solution of succinic acid was used as a precipitator, the protein precipitation degree equaled 89.3%. The paper introduces a new oat protein purification method. The optimal multiplicity of purification by RP-HPLC was 4 purification cycles. For the alkaline extract, the total content of high molecular weight fractions (50.0–120.0 kDa) was 72.7% and the total content of low molecular weight fractions (15.0–49.0 kDa) was 27.3%. For the acid extract, the total content of high molecular weight fractions was 72.9%, while the content of low molecular weight fractions was 27.1%. Oat proteins obtained by alkaline and acid extraction demonstrated a high foaming ability (148–177%) at pH = 6.0–9.0, as well as a good fat and water retention capacity. The oat proteins were found to have a high content of protein and essential amino acids similar to animal proteins. A comparative analysis showed that oat protein can act as an alternative substitute for animal proteins.